Mentoring and Supporting Our Next Generation of Women Toxicologists - Swanson, Hollie I. (Frontiers in Toxicology, 2022)
Career success of women toxicologists requires intentional strategies designed to encourage and support their professional and personal growth. Key among these are mentoring approaches which should be initiated early in their academic careers and continue as their careers progress. While undergraduate and graduate students as well as postdoctoral fellows, women engaged in all STEM fields benefit from one-on-one mentoring experiences offered by both their peers, near-peers and faculty. Here, they not only receive encouragement and lessons on “how to be a good mentee”, but also gain scientific and life skills. Networking opportunities and career planning advice are also important benefits. As woman scientists progress in their careers, they continue to benefit from one-on-one mentoring and structured career development programs adapted to meet their changing needs ultimately culminating in leadership coaching as they reach the pinnacles of their careers. While mentoring success is best facilitated by structured programs that match mentees with mentors and offer training, support and programming, the availability of these programs to women toxicologists is limited. Opportunities for women to participate in structured mentoring programs should be enhanced by institutions, funding agencies and scientific societies as a component of accelerated diversity and inclusion efforts.